Drug abuse handbook - Karch, Steven B. (CRC Press/Taylor & Francis, 2007)
Following the well-received first edition, the Drug Abuse Handbook, Second Edition is a thorough compendium of the knowledge of the pharmacological, medical, and legal aspects of drugs. The book examines criminalistics, pathology, pharmacokinetics, neurochemistry, treatment, as well as drugs and drug testing in the workplace and in sports, and the ethical, legal, and practical issues involved.